Optimization of cultivar sowing density of rice hybrids - Medeiros, Letícia; Schuch, Luis Osmar Braga; Mondo, Vitor Henrique Vaz; Magalhães Júnior, Ariano Martins de; Dörr, Caio Sippel (Revista de Ciências Agroveterinárias, 2018)
The objective of this study was to evaluate the productivity and quality of grains under different sowing densities in irrigated rice hybrids. The hybrids BRSCIRAD 302 and BRSCIRAD AH703 CL were analyzed at sowing densities of 10, 20, 30 and 40 kg ha-1, in the municipalities of Capão do Leão and Capivari do Sul, in the state of Rio Grande do Sul. The characteristics assessed were: productivity, components of grain production, agronomic characteristics, industrial and commercial quality of irrigated rice grains. The data were submitted to analysis of variance and F test, using for the comparison of hybrids the Tukey test at a 5% significance level, and for sowing, density regression analysis was applied. Sowing densities of 20 kg ha-1 and higher show no effect on productivity. The grain quality of hybrids is not influenced by the variation in sowing density, and reduction in sowing density up to 10 kg ha-1 does not affect the commercial quality of the grains. Thus, it is possible to recommend the cultivation of irrigated rice hybrids with reduced sowing densities, starting from 20 kg ha-1, without affecting grain yield and quality.